COMPARISON OF RADIOGRAPHY WRIST JOINT POSTERIOR ANTERIOR (PA) ULNAR DEVIATION CENTRAL RAY VARIATION FOR ASSESSING OS SCAPHOID - Oktavia Puspita Sari; Syandra Edo Marlindo; Heriansyah Heriansyah (Journal of Vocational Health Studies)
Background: The technique of examining the wrist joint to see abnormalities in the carpalia region, especially in the scaphoid os, there is a special technique, namely ulnar deviation with variations of the central ray 150 to 250 proximally. Purpose: to determine in which direction the light is to assess the optimal scaphoid anatomy. Methods: data retrieval is done by shooting wrst joints with 15x and 25x proximaly rays. Results: The direction of the angular ray is 15 degrees of scapoid which is free from overlapping and more informative. Conclusion: The average value of the results of the questionnaire processing is obtained on the technique with 15o ray variation of 3.2733 with a value of 0.083.